HUBUNGAN HIGIENE PERSONAL DENGAN INFEKSI KECACINGAN PADA SISWA SD BONE-BONE KABUPATEN MAMUJU SULAWESI BARAT - Ridhayani Adiningsih; Zrimurti Mappau; Nunik Desitaningsih (Jurnal Kesehatan Manarang, 2017)
Worm infection causes a big loss for patients. Approximately 60-90 percent of the Indonesian population is still suffering from worm infestation. Mamuju District Health department figures show Infection worm disease in 2012 reached 7188 inhabitants and in 2013 reached 6143 inhabitants, while in 2014 reached 4734 people. The purpose of this study to determine the relationship of personal hygiene by Infection Helminthiases. This study was an observational study with this type of cross-sectional study with data collection and observation. The sample size was 115 with technique research sampling is done with simple random sampling. Based on the results of statistical analysis known that there was no correlation between worm infection Infection with custom cut nails with sig = 0.278, use of footwear with sig = 0.119, washing habits hands with sig = 0697, Bathing regularly with sig = 0499 and the use of latrines with sig = 0872. Infection incidence Helminthiases have no connection with personal hygiene, there are many factors that can cause infections Helminthiases include socio-economic factors, knowledge, and sanitation facilities.